Down to the wire [aircraft wiring]. - Furse, C. (IEEE spectrum)
Aging, brittle wiring within aircraft poses a hidden hazard that emerging technologies aim to address. Among the most promising technologies are advanced reflectometry methods, for routine maintenance; so-called smart wire systems, for continual, on-the-spot wire testing; and arc-fault circuit breakers and advanced fire suppression techniques, for minimizing damage and injury should a fault occur. Remaining challenges include detecting the minuscule insulation breaks that encourage arcing; optimizing the benefits and mitigating the risks of the various wire testing techniques; and getting a better handle on the labyrinthine complexity of aircraft wiring systems